2014
DOI: 10.1095/biolreprod.114.121202
|View full text |Cite
|
Sign up to set email alerts
|

Functional Role of Arginine During the Peri-implantation Period of Pregnancy. II. Consequences of Loss of Function of Nitric Oxide Synthase NOS3 mRNA in Ovine Conceptus Trophectoderm1

Abstract: Nitric oxide (NO) is a gaseous molecule that regulates angiogenesis and vasodilation via activation of the cGMP pathway. However, functional roles of NO during embryonic development from spherical blastocysts to elongated filamentous conceptuses (embryo and extraembryonic membrane) during the peri-implantation period of pregnancy have not been elucidated in vivo. In order to assess roles of NO production in survival and development of the ovine conceptus, we conducted an in vivo morpholino antisense oligonucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Nitric oxide synthase 3 has been shown to be a key enzyme for NO production in ovine TE. Knockdown by using an in vivo morpholino antisense oligonucleotide for NOS3 resulted in thin, small and under developed conceptuses (Wang et al 2014b). These conceptuses also had decreased SLC7A1 message in the TE as well.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide synthase 3 has been shown to be a key enzyme for NO production in ovine TE. Knockdown by using an in vivo morpholino antisense oligonucleotide for NOS3 resulted in thin, small and under developed conceptuses (Wang et al 2014b). These conceptuses also had decreased SLC7A1 message in the TE as well.…”
Section: Discussionmentioning
confidence: 99%
“…NO, CO, and H 2 S) to regulate nutrient metabolism. 2,18,26,27 For example, dietary arginine enhances the abundance of phosphorylated mammalian target of the rapamycin (mTOR), eukaryotic initiation factor (eIF) 4E-binding protein-1 (4E-BP1), and ribosomal protein S6 kinase 1 (S6K1), as well as the formation of the active eIF4E-eIF4G complex, but reduces the abundance of the inactive 4E-BP1-eIF4E complex in skeletal muscle, leading to increased protein synthesis and whole-body growth. 28 In addition, dietary glutamine enhances intestinal integrity, cell survival, and villus height in association with activation of mTOR cell signaling, while attenuating weaning-induced reduction in occludin, claudin-1, zonula occluden (ZO)-2, and ZO-3 protein abundances.…”
Section: Regulation Of Cell Signaling Pathwaysmentioning
confidence: 99%
“…In vivo Arg-treatment enhanced placental functions during advanced stages of pregnancy in sheep [46][47][48]71,73]. Furthermore, in vitro studies have demonstrated the importance of Arg for uterine and conceptus growth and functions during the peri-implantation period of pregnancy in sheep [74][75][76]. However, very little is known about potential Arg effects on any reproductive processes, including uterine functions in nonpregnant animals.…”
Section: Revised 12mentioning
confidence: 99%